Pemenuhan Hak Anak Pasca Perceraian dalam Perspektif Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak dan Kompilasi Hukum Islam - Muhammad Luqman Asshidiq; Diana Zuhroh (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
This study is about the fulfillment of children's rights after divorce in the perspective of Law Number 35 of 2014 concerning Child Protection and the Compilation of Islamic Law. This research is motivated by problems in the family, where after the occurrence of a divorce, due to several factors the parents do not give the right to a living, maintenance and education to children as they should and prefer to be entrusted to their grandmothers or grandfathers. The data sources used in this study came from four families with the first criterion, their parents were divorced. Secondly, the child was abandoned when theywere toddlers and entrusted to their grandmother or grandfather. The results of the study indicate that in Dukuh Gandurejo, Gemolong Village, Gemolong District, Sragen Regency, parents are still obliged to fulfill children's rights including custody rights (hadanah), maintenance rights, and education even though the parents are divorced. This has been regulated in positive laws such as Law Number 35 of 2014 concerning Child Protection and the Compilation of Islamic Law as well as in the regulation explaining in detail the sanctions for parents if they do not give rights in the form of maintenance to children.